Abbott-and-Costello Numbers. (1st March 2016) - Sporn, Howard
Summary: We analyze a mathematical routine from the comedy team of Abbott and Costello and determine all possible numbers that could be used in the joke. We determine a recursive formula and a closed-form expression for the resulting integer sequence, both of which use least common multiples.